Prevention of recurrent thromboembolism in myeloproliferative neoplasms: review of literature and focus on direct oral anticoagulants: DOACs in MPNs. Issue 5 (4th July 2021) - How, Joan; Story, Charlotte; Connors, Jean Marie
ABSTRACT: Myeloproliferative neoplasms (MPNs), including polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (MF) are stem cell clonal neoplasms characterized by expansion of late myeloid cells. Thrombosis risk is elevated in MPNs and contributes significantly to morbidity and mortality. Current consensus guidelines make no specific recommendations regarding anticoagulant choice for the treatment of venous thromboembolism (VTE) in MPNs, with most evidence supporting the use of vitamin K antagonists (VKAs) for secondary prophylaxis. However, direct oral anticoagulants (DOACs) are now increasingly being used, although with limited data on safety and efficacy in MPNs specifically. The widespread adoption of DOACs is based on new, high-quality evidence demonstrating safety and efficacy of DOAC treatment for cancer-associated VTE. However, these studies include few if any MPN patients, and MPNs have disease-specific considerations that may elevate thrombosis and bleeding risk. The purpose of this review is to discuss evidence behind current treatment recommendations for thrombosis in MPNs, with special attention to the use of DOACs.